Surface parameters, biodegradability and antimicrobial activity of some amide ether carboxylates surfactants - M.M.A. El-Sukkary; N.O. Shaker; Dina A. Ismail; Sahar M. Ahmed; M.F. Zaki; Ashgan I. Awad (Egyptian Journal of Petroleum)
In the present investigation, a series of amide ether carboxylates surfactants RCO-NHCH2CH2O (CH2CH2O)6CH2COONa (AEC), with different alkyl chain lengths from (C12 to C18) and (C18=, C18==) were synthesized. The surface parameters particularly effectiveness (Πcmc), efficiency (PC20), maximum surface excess (Γmax) and minimum area per molecule (Amin) values were investigated. In addition, the standard free energies of micellization (ΔGmic0) and adsorption (ΔGads0) were calculated for the prepared surfactants in aqueous solution. The prepared surfactants were tested for their biodegradability in the water of the River Nile according to the Die-away test method. Their antimicrobial activity against strains of bacteria, yeast and fungi were also investigated.